Reasons, rights, and values - Audi, Robert, 1941- (2015)
A central concern in recent ethical thinking is reasons for action and their relation to obligations, rights, and values. This collection of recent essays by Robert Audi presents an account of what reasons for action are, how they are related to obligation and rights, and how they figure in virtuous conduct. In addition, Audi reflects in his opening essay on his theory of reasons for action, his common-sense intuitionism, and his widely debated principles for balancing religion and politics. Reasons are shown to be basic elements in motivation, grounded in experience, and crucial for justifying actions and for understanding rights. Audi's clear and engaging essays make these advanced debates accessible to students as well as scholars, and this volume will be a valuable resource for readers interested in ethical theory, political theory, applied ethics, or philosophy of action.--
Reasons, practical reason, and practical reasoning -- Intrinsic value and reasons for action -- The grounds and structure of reasons for action -- Practical reason and the status of moral obligation -- Intuitions, intuitionism, and moral judgment -- Kantian intuitionism as a framework for the justification of moral judgments -- Moral virtue and reasons for action -- Virtue ethics in theory and practice -- Wrongs withing rights -- Religion and the politics of science: can evolutionary biology be religiously neutral? -- Nationalism, patriotism, and cosmopolitanism in an age of globalization.
Includes bibliographical references and index.
Keywords: Reasoning; Virtues; Ethics; Ethics; Reasoning; Virtues